SPURS SYSTEM - Shatsova, R. B.; Anisimova, G. B. (Одеські астрономічні публікації, 2012)
The system of nearby radioloops (spurs) is the screen to the remote objects and, perhaps, it distorts the real sky picture. But it is not due to the light absorption. Vise versa, the spurs system makes the objects brighter. Perhaps, it is the main reason for the fact that the majority of different scale objects, such as supernova, bright parts of Galactic spiral arms, main filaments of Local supergalaxy, etc are observed particularly through the spurs shells. Besides, the density of spiral structure’ indicators, such as supergiants, Cepheids, and OB-associations, observed through the spurs, exceeds twice and more the same one in the neighbouring Milky Way regions. These facts can be explained either by making the objects brighter by spurs system, or by the existence of matter of higher density, contacting to spurs belts, or their combination.